PENGARUH EFEKTIVITAS KOMITE AUDIT TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN (Studi Empiris pada Perusahaan Perdagangan, Jasa, dan Investasi yang Terdaftar di BEI Tahun 2017-2019) - Hizkia Efraldo Saragih; Herry Laksito (Diponegoro Journal of Accounting, 2021)
The purpose of this research is to ecamine the effect of effectiveness of the audit committee which consists of the independence of the audit committee, the expertise of the audit committee, the size of the audit committee, the authority of the audit committee, and the gender of the audit committee on the timeliness of financial reporting. The variable used in the examination are independence of the audit committee, the expertise of the audit committee, the size of the audit committee, the authority of the audit committee, and the gender of the audit committee as the independen variables. Audit delays as the dependent variabel and also ROA and firm size as the control variables.This research used trade, service, and investment companies during 2017-2019 with total samples are 231 samples. Sampling based on purposive sampling metdhoed that follows certain criteria(s). The analysis method used in this research is Multiple regression analysis. The result of this study indicate that the independence of audit committee and the size of audit committee have a significant negative effect on the timeliness of financial repoting. Audit committee authority has a significant positive effect on the timeliness of financial reporting. While the expertise of the audit committee, the number of audit committee meetings, the gender of the audit committee had a negative but insignificant effect on the timeliness of financial reporting